Comparisons of analytical chemistry and biological activities of extracts from North Pacific gyre plastics with UV-treated and untreated plastics using in vitro and in vivo models. (December 2018) - Coffin, Scott; Dudley, Stacia; Taylor, Allison; Wolf, Douglas; Wang, Jie; Lee, Ilkeun; Schlenk, Daniel
Abstract: Plastic debris is an emerging worldwide threat to marine biota. Marine species may face unique challenges in low-flow estuarine systems with a high abundance of "macro-sized" (>4.75 mm) plastic due to the leaching of constituents and adsorbed contaminants. To simulate this leaching process, plastic samples recovered from the North Pacific Gyre along with corresponding UV-irradiated virgin plastic and non-irradiated virgin plastic counterparts were incubated in saltwater for 30 days at ambient temperatures ranging from 17 to 25 °C. Following solid-phase extraction, water samples were fractionated with sequential methanol elution from 10 to 100% and evaluated using in vitro assays assessing estrogen receptor (ER) and aryl hydrocarbon receptor (AhR) activities. In vivo responses (vitellogenin [ vtg ] and cytochrome p 450 1A [ cyp1a ] mRNA) were measured following 5-day exposures in Japanese medaka ( Oryzias latipes ) larvae (3 days post hatch). Estrogenic plasticizers, co-planar PCBs and PAHs were quantified in the extracts using targeted GC–MS/MS and UPLC-MS/MS. In vitro estrogenicity showed highest activity in the 70% methanol fraction for all plastic leachate exposures. Whole extract in vitro estradiol equivalent (EEQ) values were 4.34 ± 2.65, 8.79 ± 2.09 and 13.78 ± 3.64 ng/L, for virgin plastic, UV-irradiated virgin plastic and North Pacific Gyre-recovered plastic, respectively (mean ± SD). Significant vtg induction was observed in medaka larvae exposed to leachate extracts from North Pacific Gyre-recovered plastic and UV-irradiated virgin plastic (9.9-fold, p  = 0.039 and 10.1-fold, p  = 0.042, respectively). Chemically-determined EEQ values were also localized in the 70% methanol fraction. Whole leachate extract chemical EEQ values were 0.33 ± 0.07, 1.64 ± 0.62 and 11.4 ± 2.13 ng/L, for virgin plastic, UV-irradiated virgin plastic and North Pacific Gyre-recovered plastic, respectively. In-vitro AhR activity was highest in the 70% methanol elution with greater activity in North Pacific Gyre-recovered plastic than in virgin plastic and UV-irradiated virgin plastic (toxic equivalency [TEQ] = 1.06 ± 0.54, 0.38 ± 0.07 and 0.71 ± 0.47 ng/L, respectively). CYP1A mRNA was significantly induced in larval medaka exposed to North Pacific Gyre-recovered plastic leachates (17.8-fold, p  = 0.02) while exposure to virgin plastic and UV-irradiated virgin plastic leachates caused no significant change. Chemically-determined TEQ analysis for AhR indicated highest activity in the 90% methanol fraction for all leachates, with whole extract in vitro TEQs being 1.47 ± 0.87, 0.03 ± 0.05 and 0.42 ± 0.38 ng/L for North Pacific Gyre-recovered plastic, virgin plastic and UV-irradiated virgin plastic, respectively. These results indicate that weathering and UV radiation release estrogenic plasticizers and demonstrate the ability for plastics to transport adsorbed persistent organic pollutants at eco-toxicologically relevant concentrations. Graphical abstract: Highlights: North Pacific Gyre plastic leached higher in vitro and chemical EEQ and TEQ than "virgin" and irradiated "virgin" plastic. North Pacific Gyre plastic leachates significantly induced cyp1a and VTG mRNA in Oryzias latipes . UV radiation enhanced desorption of BPA, OP and PCBs from virgin plastic and induced VTG mRNA in Oryzias latipes .